Cost-Effectiveness of a Programme to Detect and Provide Better Care for Female Victims of Intimate Partner Violence - Norman, Richard; Spencer, A.; Eldridge, S.; Feder, G. (Sage Publications Ltd., 2010)
Objective: Primary care clinicians often fail to detect women who are victims of intimate partner violence (IPV). Our aim was to investigate the cost-effectiveness of a programme in primary care to detect and support such women. Methods: We developed a Markov model to estimate the cost-effectiveness of education and support for primary care clinicians to increase their identification of survivors of IPV and to refer them to a specialist advocacy agency or a psychologist with specialist skills. The programme was implemented in three general practices in the United Kingdom (with an additional practice acting as a control) and provided cost data and rates of identification and referral. Other cost data and the effectiveness of IPV advocacy came from published sources. Results: The model gave an incremental cost-effectiveness ratio (ICER) of approximately £2,450 per quality adjusted life year (QALY). Although the ratio increased in some of the sensitivity analyses, most were under a conventional willingness to pay threshold (£30,000/QALY).Conclusions: While there is considerable uncertainty in the underlying parameters, a training programme for primary care teams to increase identification and referral of women experiencing IPV is likely to be cost effective.